PENGGUNAAN RASCH MODEL UNTUK MENGANALISIS AITEM INSTRUMEN STRES PENGASUHAN ORANG TUA ANAK USIA DINI - Rahmaningtyas, Putri Andita; Agustin, Mubiar; Dahlan, Tina Hayati (Jurnal Muara Pendidikan, 2025)
This study aims to analyze the items on the parenting stress instrument for parents of early childhood. The items analysis process was carried out with the Rasch Model approach using the Winstep application. This instrument consists of three main dimensions, namely: Parental Factors, Family Environment, and Available Resources, which consists of 50 items. Based on the results of the analysis, 25 items were obtained that met the criteria for item analysis. The results of this analysis show that the reliability item value is (0.98), this means that the items are very good for use in parenting stress instruments. This parenting stress instrument has the potential to assist in measuring parenting stress levels in the context of early childhood parenting. In addition, the use of this instrument can support the implementation of scientific research, intervention development, and policy formulation oriented towards improving family wellbeing and optimal early childhood development.